Non-templated hydrothermal growth of anisotropic magnetite nanostructures using hexamine as the directing agent - Bhagwat, S. V.; Jouen, Samuel; Kundaliya, D. C.; Singh, H.; Jagadale, Tushar C.; Athawale, A. A.; Lofland, S. E.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2009)
Anisotropic growth of magnetite (Fe(3)O(4)) nanoparticles is achieved in a hydrothermal growth process using hexamine to play a dual role of oxide forming and directing agent. The samples are characterized by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, squid magnetometry, ferromagnetic resonance technique, diffuse reflectance spectroscopy and Mossbauer spectroscopy, which collectively establish the formation of Fe(3)O(4) phase. Anisotropic structures such as nanorods and nanotubules are revealed and these are shown to exhibit good humidity sensing properties.
Keywords: Anisotropic Nanostructures; Hexamine; hydrothermal; magnetite; Mossbauer